Hypertension and ethnicity. (July 2016) - Bennett, Amanda; Parto, Parham; Krim, Selim R.
Abstract : Purpose of review: Despite its continued increase in prevalence in minorities, data regarding hypertension (HTN) control among such ethnic groups remains limited. This review highlights the most recent literature on the epidemiology, prevalence, and treatment strategies of HTN among four racial groups (non-Hispanic Whites (NHW), Blacks, Hispanics, and Asians). Recent findings: Overall awareness and treatment of HTN were found to be higher in blacks when compared with NHWs. Access to health insurance is associated with successful HTN control, particularly among the Hispanic populations. Recent data from SBP Intervention Trial suggests the blood pressure control and adherence rates in blacks were highest among men, with a higher number of comorbidities, and on diuretic therapy. Additionally, the initiation of thiazide-type diuretics and calcium channel blocker was superior to β-adrenergic blockers and angiotensin converting enzyme inhibitor/angiotensin receptor blockers in blood pressure lowering among blacks. However, no specific treatment recommendations exist for Hispanics or Asians. Finally, recent guidelines from the Joint National Commission recommend initial treatment with a thiazide-type diuretic regardless of race. Summary: Despite recent progress, racial disparities in awareness and treatment of HTN continue to exist. To reduce this important gap, future research should focus on epidemiologic, genetic, and sociologic factors as well as specific therapies to achieve maximum medical benefit in these subgroups.